Perbedaan kadar antitrombin III pada sepsis neonatal kultur darah positif dan kultur darah negatif - Prima Indah Siridian; Ricke Loesnihari; Guslihan Dasa Tjipta (DiscoverSys Inc., 2019)
Background: Fetal and neonatal hemostatic systems are dynamic. Coagulation and inhibitors of coagulation factors are progressively synthesized by the fetus which begins after 34 weeks of pregnancy and at the initial hours after birth. The neonatal hemostatic system generally shifts towards hypercoagulability. During sepsis, this hypercoagulability is exacerbated by an imbalance of coagulation and inhibitors of coagulation factors including antithrombin III. This study aimed to determine differences of antithrombin III levels in neonatal sepsis positive blood cultures (proven sepsis) and negative blood cultures (unproven sepsis).Methods: The subjects of this study were 26 patients of neonatal sepsis, which consisted of 13 positive blood cultures and 13 negative blood cultures. Levels of antithrombin III were examined by chromogenic methods. Examination of blood cultures of gram-positive bacteria using manual method and gram-negative bacteria using semiautomatic method. Data analysis uses an independent t test.Results: Antithrombin III levels in neonatal sepsis patients positive blood culture (73,23 ± 21,62) didn’t differ significantly compared to negative blood cultures (65,63 ± 20,81) with p = 0,370 (p> 0,05). The bacterial pattern that caused neonatal sepsis were Staphylococcus sp. (84,6%), CoNS (81,8%), Staphylococcus aureus (18,2%), Salmonella spp (7,7%) and Klebsiella pneumoniae ssp pneumoniae (7,7%). The sensitivity pattern of Staphylococci to cefoxitin to determine resistence, found 5 Methicillin-resistant Staphylococci (MRS) and 1 Meticillin-resistant Staphylococcus aureus (MRSA). Conclusion: There were no significant differences of antithrombin III levels in neonatal sepsis positive blood cultures and negative blood cultures.